2020
DOI: 10.1039/d0tc03712e
|View full text |Cite
|
Sign up to set email alerts
|

Tunable valley splitting and anomalous valley Hall effect in VTe2/Ga2S3 heterostructures

Abstract: The modulation of valley splitting is not only of fundamental interest but also crucial to valleytronics. Generally, valley splitting stems from spin-orbit coupling and the absence of time-reversal symmetry which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…16 Our prior work demonstrated that valley carriers with different spins can distribute in different layers by reversing the ferroelectric polarization of the substrate in the VTe 2 /Ga 2 S 3 heterostructure. 17 Meanwhile, the layer Hall effect with electrons from the top and bottom (btm) layers spontaneously deflecting in opposite directions was also observed in 2D topological axion antiferromagnet MnBi 2 Te 4 . 18 Additionally, valley polarization can also be realized via the valley selective circular dichroism effect where only the electrons in the K (K′) valley are excited by left- (right-) polarized light, 2,6,19 as demonstrated in many 2D materials without T , such as transition metal dichalcogenides (TMDs).…”
Section: Introductionmentioning
confidence: 89%
“…16 Our prior work demonstrated that valley carriers with different spins can distribute in different layers by reversing the ferroelectric polarization of the substrate in the VTe 2 /Ga 2 S 3 heterostructure. 17 Meanwhile, the layer Hall effect with electrons from the top and bottom (btm) layers spontaneously deflecting in opposite directions was also observed in 2D topological axion antiferromagnet MnBi 2 Te 4 . 18 Additionally, valley polarization can also be realized via the valley selective circular dichroism effect where only the electrons in the K (K′) valley are excited by left- (right-) polarized light, 2,6,19 as demonstrated in many 2D materials without T , such as transition metal dichalcogenides (TMDs).…”
Section: Introductionmentioning
confidence: 89%
“…[65] The details of the valley-polarized QAHE will be discussed in the next section. In recent years, there have been many works to realize the electrical control of valley DOF by forming heterostructures between multiferroic materials and other materials, [28,[66][67][68][69][70][71] such as AgBiP 2 S 6 /CrBr 3 vdW heterostructures with ferromagnetism, ferroelectricity and valley behavior. At the minimum of the conduction band located at the +K/ − K point, a spin splitting of 423.1 meV occurs.…”
Section: -9mentioning
confidence: 99%
“…22 Realizing the nonvolatile electric field control of the AVH effect is of great significance for designing nonvolatile memory and switching devices using the valley degree of freedom. 23 A van der Waals heterostructure [24][25][26][27] allows integrating materials with distinct properties. Constructing a heterostructure is a simple and easy way to couple FE and ferrovalley, through which the AVH effect can be controlled via applying an a State Key Laboratory of Solidification Processing, Center for Advanced Lubrication electrical field.…”
Section: Introductionmentioning
confidence: 99%
“…A van der Waals heterostructure 24–27 allows integrating materials with distinct properties. Constructing a heterostructure is a simple and easy way to couple FE and ferrovalley, through which the AVH effect can be controlled via applying an electrical field.…”
Section: Introductionmentioning
confidence: 99%